Cost-Effectiveness Analysis of Third-Generation Cephalosporin Antibiotics in the Treatment of Typhoid Fever at Tangerang Selatan General Hospital - Widya Pratama, Mochammad; Winarni, Gandes; Ayu Utari, Luthfinawa (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
Typhoid fever is an acute systemic infectious disease caused by Salmonella typhi bacteria that infect through contaminated food or drink. In the treatment of typhoid fever, antibiotic therapy is needed. Third-generation cephalosporin antibiotics are antibiotics used as second-line treatment in typhoid fever. Differences in antibiotic use can increase costs incurred by patients, so a cost-effectiveness analysis is needed to determine the most effective and efficient treatment. The purpose of this study was to determine the cost effectiveness of third-generation cephalosporin antibiotics in patients with typhoid fever hospitalized in South Tangerang City Hospital in 2023. The research method in this study is descriptive method with purposive sampling technique. This research design uses a non-experimental design. This study was conducted in April-May 2024 at the South Tangerang City Hospital using secondary data in the form of medical record data and medical cost data as research instruments. The number of samples in this study were 127 samples that met the inclusion criteria. The third-generation cephalosporin antibiotics used were ceftriaxone and cefixime. Cost-effectiveness is expressed in ACER (Average Cost-Effectiveness Ratio) which is obtained from the average total direct medical costs divided by the average clinical outcome. The results showed the ACER value of cefixime Rp.767,866/day for length of hospitalization and Rp.1,122,611/day for fever-free time, ACER value of ceftriaxone Rp.711,349/day for length of hospitalization and Rp.985,726/day for fever-free time, ACER value of ceftriaxone + cefixime antibiotic combination Rp.763,054/day for length of hospitalization and Rp.1,051.146/day for fever-free time. The conclusion of this study is that the most cost-effective third-generation cephalosporin antibiotic is ceftriaxone.